2001
DOI: 10.1038/sj.bmt.1703149
|View full text |Cite
|
Sign up to set email alerts
|

Decreased bone mineral density is common after autologous blood or marrow transplantation

Abstract: Summary:Survivors of autologous blood or marrow transplantation (ABMT) are predisposed to decreased bone mineral density (BMD), but data are lacking on the incidence and risk factors for this condition. Therefore, we measured BMD in 64 of 68 consecutive ABMT survivors (35 men and 29 women) attending the University of Toronto ABMT long-term follow-up clinic. Patients were evaluated a median of 4.2 years (range: 4.9 months-11.4 years) after ABMT. Median age at evaluation was 49.6 years (range: 23.5-68.2 years). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
27
2
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 27 publications
5
27
2
1
Order By: Relevance
“…The demonstration of significant bone loss at the proximal femur, but not at the spine, is consistent with the findings reported by Schimmer et al (2001), and a similar distribution of bone loss has also been documented following liver transplantation (Hussaini et al, 1999;Keogh et al, 1999;Ninkovic et al, 2002). The mechanisms underlying this differential bone loss have not been established nor is it known whether complete recovery of bone mass occurs over longer periods of time.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The demonstration of significant bone loss at the proximal femur, but not at the spine, is consistent with the findings reported by Schimmer et al (2001), and a similar distribution of bone loss has also been documented following liver transplantation (Hussaini et al, 1999;Keogh et al, 1999;Ninkovic et al, 2002). The mechanisms underlying this differential bone loss have not been established nor is it known whether complete recovery of bone mass occurs over longer periods of time.…”
Section: Discussionsupporting
confidence: 85%
“…Many of these patients are still relatively young at the time of autoSCT and have been exposed to a range of processes that may predispose to bone loss and an increased risk of fragility fractures (Weilbaecher, 2000). A recent cross-sectional analysis in long-term survivors following autoSCT (BMD measured at a median 4AE2 years) found reduced BMD values compared with age-matched healthy control subjects at the femoral neck but not the lumbar spine (Schimmer et al, 2001). Hitherto, however, there have been no large prospective studies addressing this group of transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to most previous studies in BMT recipients, 10,11,13,15 no patient in our cohort met the WHO criteria for osteoporosis whereas about one half of our BMT survivors had evidence of osteopenia. So far, only one investigation performed 75 months after allogeneic BMT 14 reported no patient with osteoporosis while 7/26 (27%) survivors had osteopenia.…”
Section: Discussioncontrasting
confidence: 49%
“…Bone mineral density (BMD) measurements about 4 years after autologous blood or marrow transplantation showed that 26 and 2% of patients had osteopenia and osteoporosis at the lumbar spine, respectively, and 46 and 8% of patients had osteopenia and osteoporosis at the femoral neck, respectively. 15 In contrast, Keilholz and co-workers 16 reported no reduction of BMD 5 years after autologous BMT. However, studies on autotransplants may not necessarily be applicable to allotransplant patients, since the latter require immunosuppressive therapy.…”
mentioning
confidence: 99%